2022
DOI: 10.1002/sstr.202200102
|View full text |Cite
|
Sign up to set email alerts
|

2D MXene Nanomaterials: Synthesis, Mechanism, and Multifunctional Applications in Microwave Absorption

Abstract: Scheme 1. a) Schematic diagram of obtaining MXene nanoflakes by adopting a certain etching strategy. b) Schematic diagram of the potential EMA mechanism analysis of MXene structure. c) Schematic illustration of the multifunctional application of MXene composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(87 citation statements)
references
References 140 publications
0
87
0
Order By: Relevance
“…4a, the ε′ values of all composites show a downward tendency in the range of 2-18 GHz attributed to the Debye relaxation. [36][37][38] When an external EM field is applied, the dipoles existing in the composites cannot change their orientations quickly to adapt to the alternating EM field and realize the rearrangement. Then the complex permittivity tends to decrease with the increase of frequency.…”
Section: Resultsmentioning
confidence: 99%
“…4a, the ε′ values of all composites show a downward tendency in the range of 2-18 GHz attributed to the Debye relaxation. [36][37][38] When an external EM field is applied, the dipoles existing in the composites cannot change their orientations quickly to adapt to the alternating EM field and realize the rearrangement. Then the complex permittivity tends to decrease with the increase of frequency.…”
Section: Resultsmentioning
confidence: 99%
“…24 Numerous studies have demonstrated that when both the core and shell are made from magnetic materials, the magnetic coupling effect generated between them could reduce the magnetic loss. 25,26 Therefore, a carbon-encapsulated magnetic material with a core-shell structure is a worthy strategy to investigate.…”
Section: Introductionmentioning
confidence: 99%
“…This has been done by developing microwave absorption materials (MAMs). 4,5 Hierarchical microstructures 6 (e.g., foam, 7 core shells, 8,9 multilayers, 10,11 carbon aerogels, 12 hollow structures 13,14 ) in microwave absorbents have become potential candidates for rich interfacial scattering and interfacial polarization. Nevertheless, the complicated synthetic steps and high energy consumption hamper large-scale application.…”
Section: Introductionmentioning
confidence: 99%